The development and assessment of alternative techniques to improve the agronomic value of Dorowa phosphate rock (Zimbabwe) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Soil Science, School of Agriculture and Environment, College of Sciences, Massey University Palmerston North, New Zealand - Tumbure, Akinson (Massey University, 2021)
Agronomically effective P fertilisers are unavailable to most smallholder farmers in Zimbabwe due to the high costs of manufacture and transportation. While phosphorus (P) deficiency remains widespread in these smallholder farming areas, farmers have limited options to ameliorate their soils leading to recurring food insecurity problems. The aim of this thesis was to develop alternative P sources with good agronomic value using locally available materials and alternative techniques such as thermal alteration, co-pyrolysis, and acid leaching. In-order to design alternative techniques, chemical and physical characterisation of the local Dorowa phosphate rock (DPR) was conducted. The DPR contained 89% and 3.5% apatite (hydroxy-fluorapatite) and calcite (CaCO₃) respectively and had a total P (TP) content of 16.5%. With less than 13.5% of TP soluble in 2% citric acid, DPR has limited agronomic value as a direct application phosphate rock. The cadmium (Cd) and fluoride (F) content in DPR was low at 0.16 mg kg⁻¹ and 2% respectively, indicating reduced F and Cd soil contamination issues in final fertiliser products. The DPR generally contained about half the amount of Fe, Al, Mg and K that is reported in literature and this was because the current sample contained less gangue materials. When compared to previous reports on DPR, the observed differences in the current sample were likely as a result of improvements in the mining and beneficiation process, or the current grade of the ore had a higher apatite content. To improve the agronomic value of DPR, the effect of thermal alteration of DPR in the presence of silicate materials (dunite, serpentine and recycled glass) was investigated. Sintering (heating at sub fusion temperatures) was chosen as a less energy intensive process compared to fusion. The sintered DPR mixtures (50% initial DPR content) had an increase of citric soluble P of up to 45, 53, and 73% when mixed with dunite, serpentine and recycled glass, respectively, compared to the unamended DPR. Increases in citric soluble P suggested isomorphous substitution of PO₄³⁻ in fluoro-hydroxyapatite by SiO₄⁴⁻ and or Mg²⁺/Na⁺ for Ca²⁺ and Fe²⁺. The sintered products that had high citric soluble P indicated that they might have improved agronomic value and were recommended for further testing in a glasshouse. Another technique where the DPR was added to maize stover residues (stems + leaves) and pyrolysed at 450 oC was developed and assessed for potential to improve the agronomic value of DPR. A suite of biochar-based fertilisers (BBFs) were obtained from pyrolysis of DPR + maize residues mixed at w/w ratios of 1:2, 1:4, 1:6, and 1:8 (DPR/ maize residues). Except for the 1:2 mixture, co-pyrolysis DPR with maize stover resulted in increases in biochar yield, carbon retention and nitrogen retention of at least 26, 43, and 26% respectively, compared to the pyrolysis of maize stover alone. The 1:6 and 1:8 mixtures produced biochar with more than a 30% increase in citric soluble P compared to the unamended DPR. The results showed that there was potential for on-farm co-pyrolysis of crop wastes with DPR to produce a P source with greater agronomic value. From these results, the 1:6 mixture that had 5.6% total P and 33.6% of the total P citric soluble, was recommended for testing in the glasshouse. The potential of using pyrolysis condensate as a cheaper acid source to recover P from DPR using sequential extractions was also evaluated. Before pyrolysis condensate could be used there was need to ascertain how much P could be recovered from DPR by the common organic acids; citric, acetic, and oxalic acids at various pH values, and then sequentially leached. Results showed that a suspension pH of 3 was necessary for maximum P recovery with citric and oxalic acids solubilising about 21.9 and 46.3% of the total P in DPR respectively, after 3 extractions. The greater P recovery under oxalic acid was attributed to the acid’s ability to remove Ca from solution as evidenced by the Ca:P molar ratio in oxalic acid leachates, which was at least 3 times less than that of other acids tested. Given this potential, a mixture of organic acids in pyrolysis condensate produced from maize stover were evaluated for their P recovery ability. Despite the high acidity and a pH of 3 maintained in leachates, sequential leaching extractions with the aqueous phase pyrolysis liquid over 26 hours was relatively ineffective, solubilising less than 14% of the total P in DPR. Four of the alternative P sources that were developed exhibited high potential agronomic value and were further evaluated for agronomic effectiveness in the glasshouse using broccoli and ryegrass as test crops. After 6 harvests, ryegrass that had been fertilised with DPR: biochar (1:6) or sintered DPR + recycled glass (50%), had similar P uptake and produced at least 95% of the biomass produced when monocalcium phosphate (MCP) was applied at the same citric soluble P rate. The same alternative P sources produced broccoli biomass yields and P uptake that was either comparable to or higher than when MCP was applied. The DPR co-pyrolysis biochar and recycled glass (50%) sintered P sources would provide a good option for smallholder farmers around the Dorowa area in Zimbabwe where PR is mined. However, larger scale field studies are recommended.
Listed in 2021 Dean's List of Exceptional Theses
Keywords: Phosphatic fertilizers; Phosphate rock; Zimbabwe; Dean's List of Exceptional Theses; 300204 Agricultural management of nutrients